THE DEVELOPMENT OF PRO ENVIRONMENTAL BEHAVIOR RESEARCH IN INDONESIA: A LITERATURE REVIEW - Laura Turena; Budiaman Budiaman; Oot Hotimah (SOSIOEDUKASI, 2026)
Environmental problems in Indonesia are increasing, which is caused by human behavior is a challenge in itself, therefore the way we act needs to adopt pro-environmental behavior. Research on pro-environmental behavior is dominated by the use of literature review from a few years, which relates to critical validity problems. The present review aims to acquaint researchers across disciplinary borders with the behavioral paradigms developed to study pro-environmental behavior in different domains.A paper provides a literature review pro environmental behavior across Indonesia using Google scholar indexded Sinta in 2023. Among, Many publication the most dominant research designed was quantitative and has been done in Java. in research requires not only one group but by many age groups. Unfortunately, the category of respondents of many is the age of millennials and gen z, which are students or college students. Based on the research findings, several recommendations have been proposed for future research. These recommendations include that the research method used should be qualitative or mixed methods and the respondents used should be elderly or older adults. Research should not be concentrated in major cities in Indonesia but spread to other cities.